Brain Plasticity in Mammals: An Example for the Role of Comparative Medicine in the Neurosciences - La Rosa, Chiara; Bonfanti, Luca (Frontiers in Veterinary Science, 2018)
Comparative medicine deals with similarities and differences between veterinary and human medicine. All mammals share most basic cellular and molecular mechanisms, thus justifying murine animal models in a translational perspective; yet “mice are not men”, thus some biases can emerge when complex biological processes are concerned. Brain plasticity is a cutting-edge, expanding topic in the field of Neurosciences with important translational implications, yet, with remarkable differences among mammals, as emerging from comparative studies. In particular, adult neurogenesis (the genesis of new neurons from brain stem cell niches) is a life-long process in laboratory rodents but a vestigial, mostly postnatal remnant in humans and dolphins. Another form of “whole cell” plasticity consisting of a population of “immature” neurons which are generated prenatally but continue to express markers of immaturity during adulthood has gained interest more recently, as a reservoir of young neurons in the adult brain. The distribution of the immature neurons also seems quite heterogeneous among different animal species, being confined within the paleocortex in rodents while extending into neocortex in other mammals. A recent study carried out in sheep, definitely showed that gyrencephalic, large-sized brains do host higher amounts of immature neurons, also involving subcortical, white and gray matter regions. Hence, “whole cell” plasticity such as adult neurogenesis and immature neurons are biological processes which, as a whole, cannot be studied exclusively in laboratory rodents, but require investigation in comparative medicine, involving large-sized, long-living mammals, in order to gain insights for translational pourposes.